Pediatric Nonceliac Gluten Sensitivity: A Gluten-related Disorder Treatment Center Experience. Issue 2 (August 2019) - Camhi, Stephanie S.; Sangal, Kajal; Kenyon, Victoria; Lima, Rosiane; Fasano, Alessio; Leonard, Maureen M.
ABSTRACT: Objective: The aim of the study was to identify the prevalence and clinical characteristics of children with nonceliac gluten sensitivity (NCGS) presenting to a tertiary care center specialized for evaluation of gluten-related disorders. Methods: The medical records of all patients aged 0 to 18 years who presented to our center over a 4-year period (July 2013–June 2018) and consented to participate in our research registry were reviewed. Patients meeting the clinical criteria for NCGS were reviewed in detail. Results: Among 500 pediatric patients who volunteered to participate in the registry during the study period, we identified 26 (5.2%) with NCGS. Both gastrointestinal and extraintestinal symptoms associated with gluten ingestion were common with abdominal pain (57.7%), bloating (53.9%), rash (53.9%), diarrhea/loose stool (42.3%), and emotional/behavioral issues (42.3%) emerging as the predominant complaints. In addition, children with NCGS demonstrated a high personal history (61.5%) and family history (61.5%) of concomitant allergic/atopic disease. Conclusions: Even within our highly specialized population of patients with a suspected gluten-related disorder, pediatric NCGS is relatively uncommon. The estimated prevalence and clinical features mirror those previously reported in a similarly highly selective population of adults. In the absence of celiac disease, clinical suspicion for NCGS should arise in a child with gastrointestinal and/or extraintestinal complaints alleviated with gluten removal and considered in symptomatic patients with associated allergic/atopic disease. Proper and adequate exclusion of celiac disease and other potential causes of the clinical complaints is essential to justify adoption of the gluten-free diet according to an appropriate stringency and with dietitian supervision to avoid nutritional deficiencies.